Beyond clinical trials – The cost saving associated with dapagliflozin use in Portugal hospital clinical practice - Dulce Brito; Cândida Fonseca; Fátima Franco; Vanessa Lopes; Sara Gonçalves; Rui Baptista; Joana Sequeira; Irene Marques; Rita Rego; Joana Pimenta; José Silva-Cardoso; Margarida Lopes; et al. (Revista Portuguesa de Cardiologia)
Introduction and objectives: Heart failure (HF) is a clinical syndrome associated with substantial morbidity, mortality, and healthcare costs. Dapagliflozin has proven efficacy in reducing the risk of death and hospitalization in HF patients, regardless of left ventricular ejection fraction (LVEF). This paper aimed to project the potential impact of dapagliflozin on healthcare costs related to HF subsequent hospitalizations (HFHs) in Portuguese hospitals. Methods: The total number of HF-related hospitalizations (hHF), HFHs, and the average length of stay for patients with a primary diagnosis of HF from six Portuguese hospitals, between January 2019 and December 2021, were collected and aggregated by hospital classification. Costs associated with HFHs were calculated according to Portuguese legislation and considering conservative, average, and complex approaches. Cost-saving projections were based on extrapolations from hHF risk reductions reported in dapagliflozin clinical trials. Results: Considering a 26% risk reduction in hHF reported on pooled-analysis of DAPA-HF and DELIVER as the expected reduction in HFHs, the use of dapagliflozin would be associated with cost savings ranging from EUR 1 612 851.54 up to EUR 6 587 360.09, when considering all hospitals and the different approaches, between 2019 and 2021. A similar projection is observed based on 24% RRR derived by weighting DAPA-HF and DELIVER sub-analyses and PORTHOS epidemiological data. Conclusions: In this projection, dapagliflozin use in all eligible hHF patients is associated with a significant reduction in direct costs. Our data support that, in addition to the improvements in HF-related outcomes, dapagliflozin may have a significant economic impact on healthcare costs in Portuguese hospitals. Resumo: Introdução e objetivos: A insuficiência cardíaca (IC) é uma síndrome clínica associada a uma elevada morbidade, mortalidade e despesa com custos de saúde. A dapagliflozina demonstrou ser eficaz na redução do risco de morte e hospitalização em doentes com IC, independentemente da fração de ejeção do ventrículo esquerdo. Este artigo visa projetar o potencial impacto da dapagliflozina na redução dos custos relacionados com hospitalizações subsequentes por IC em hospitais portugueses. Métodos: Foi recolhido, e posteriormente analisado de forma agregada em clusters, o número total de hospitalizações por IC, hospitalizações subsequentes por IC e duração média de internamento dos doentes com diagnóstico primário de IC em seis hospitais portugueses, entre janeiro de 2019 e dezembro de 2021. Os custos relacionados com hospitalizações subsequentes por IC foram calculados de acordo com a legislação portuguesa e tendo em consideração três abordagens – conservadora, média e complexa. A projeção da redução de custos teve por base as reduções do risco relativo (RRR) de hospitalizações por IC (hIC) reportadas nos ensaios clínicos com dapagliflozina. Resultados: Considerando uma RRR de 26% do risco de hospitalização subsequente por IC, com base no valor reportado na análise agregada dos estudos DAPA-HF e DELIVER relativa à RRR de hIC, a nossa projeção indica que a utilização da dapagliflozina resulta numa redução de custos. De acordo com a nossa projeção a redução de custos oscila entre €1,612,851.54 e €6,587,360.09, entre 2019 e 2021, ao considerar todos os hospitais envolvidos e as diferentes abordagens metodológicas. A projeção aponta para um resultado similar tendo por base uma RRR de 24%, resultante da ponderação das subanálises de DAPA-HF e DELIVER, juntamente com dados epidemiológicos do estudo PORTHOS. Conclusões: Nesta projeção, a utilização de dapagliflozina, em todos os doentes hospitalizados por IC que sejam elegíveis, está associada a uma redução direta significativa nos custos hospitalares. Estes dados reforçam a ideia de que, para além da melhoria nos resultados de saúde relacionados com a IC, a dapagliflozina pode ter um impacto significativo nos hospitais portugueses ao nível dos custos de saúde.